The Influence of Green Banking and Corporate Social Responsibility on Financial Performance - Nyoman Ayu Dian Lestari; Ida I Dewa Ayu Mas Manik Sastri; Luh Kade Datrini (International Journal of Islamic Business and Management Review, 2026)
This study aims to examine the influence of Green Banking and Corporate Social Responsibility (CSR) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) in 2024. The study employs a quantitative approach using secondary data derived from annual reports and sustainability reports. From a population of 47 banks, 31 companies were selected through purposive sampling after excluding outliers. Financial performance is proxied by Return on Assets (ROA), while Green Banking and CSR are measured using the Green Banking Disclosure Index (GBDI) and Corporate Social Responsibility Disclosure Index (CSRDI) based on Global Reporting Initiative (GRI) standards. Data were analyzed using multiple linear regression with SPSS software. The results indicate that Green Banking has no significant effect on financial performance, whereas CSR has a positive and significant effect on ROA. The findings suggest that while sustainable banking practices may require a longer time horizon to generate measurable financial returns, effective CSR implementation contributes directly to improved profitability. This study provides empirical evidence on sustainable finance practices in Indonesia and offers insights for banking management and regulators in strengthening sustainability-oriented strategies.